Prevalence and determinants of antepartum depressive and anxiety symptoms in expectant mothers and fathers: results from a perinatal psychiatric morbidity cohort study in the east and west coasts of Malaysia - Nasreen, Hashima E; Ab Rahman, Jamalludin; Mohd Rus, Razman; Kartiwi, Mira; Sutan, Rosnah; Edhborg, Maigun (Springer Nature, 2018)
Background: Research on antepartum psychiatric morbidities investigating depressive and anxiety symptoms in expectant mothers and fathers is lacking in low- and middle-income countries. This study aimed to estimate the prevalence of antepartum depressive, anxiety and co-occurring significant symptoms and explore the associated factors in a cross-section of Malaysian expectant mothers and fathers. Methods: We used cross-sectional data from a prospective cohort study of 911 expectant mothers and 587 expectant fathers during their third trimester of pregnancy, from health clinics of two states in the east and west coasts of Malaysia. The validated Malay version of Edinburgh Postnatal Depression Scale and the anxiety sub-scale of Depression, Anxiety and Stress Scale were used to measure the depressive and anxiety symptoms. Multiple logistic regression analyses identified the determinants of antepartum depressive and anxiety symptoms (ADS and AAS). Results: Prevalence of ADS was 12.2% in expectant mothers and 8.4% in expectant fathers, while AAS was 28.8% in expectant mothers and 13.3% in expectant fathers, and co-occurring significant symptoms was 8.0% in expectant mothers and 4.0% in expectant fathers. Expectant mothers and fathers having perceived social/family support were less likely to suffer from ADS. Intimate partner violence, poor relationship with husbands, depression in earlier pregnancy and husband’s depression in current pregnancy in expectant mothers, and living in rented house, sex preference for the unborn child, stressful life events and wife’s depression in current pregnancy in expectant fathers were associated with a greater likelihood of ADS. The determinants for AAS were living in rented house and with parents/in-laws, poor relationship with husbands, restrictions during pregnancy and stressful life events for expectant mothers, and stressful life events and being unsupportive towards wives in household chores for expectant fathers. Conclusion: Both ADS and AAS are prevalent in expectant mothers and fathers, and largely an undetected problem in Malaysia. Administration of couple-based screening and referral program during antenatal check-up should be universal practices to identify and treat the psychiatric morbidities.